2023
DOI: 10.3390/ma16186280
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of ODS FeCrAl Alloys–A Review of Composition Design

Xi Wang,
Xinpu Shen

Abstract: After the Fukushima nuclear accident, the development of new accident-tolerant fuel cladding materials has become a research hotspot around the world. Due to its outstanding corrosion resistance, radiation resistance, and creep properties at elevated temperatures, the oxide dispersion strengthened (ODS) FeCrAl alloy, as one of the most promising candidate materials for accident-tolerant fuel cladding, has been extensively studied during the past decade. Recent research on chemical composition design as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 171 publications
(334 reference statements)
0
3
0
Order By: Relevance
“…This is attributed to the ultra-fine grain structure, which facilitates oxygen diffusion and increases the oxidation rate. Numerous studies have shown that chromium (Cr) could form a compact oxide film on the surface of stainless steel, which can prevent the further diffusion of O element in the alloy and enhance the oxidation resistance of stainless steel [31][32][33][34][35]. However, the effect of adding Cr on the performance of ODS-Mo alloys remains unclear and requires further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the ultra-fine grain structure, which facilitates oxygen diffusion and increases the oxidation rate. Numerous studies have shown that chromium (Cr) could form a compact oxide film on the surface of stainless steel, which can prevent the further diffusion of O element in the alloy and enhance the oxidation resistance of stainless steel [31][32][33][34][35]. However, the effect of adding Cr on the performance of ODS-Mo alloys remains unclear and requires further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent this crisis, researchers tend to pursue new materials for fuel cladding [1,2]. The FeCrAl alloy emerged as a promising candidate for fuel cladding in nuclear power plants due to its excellent high-temperature oxidation resistance, radiation resistance, and mechanical properties [3][4][5][6][7]. People have carried out a series of studies on FeCrAl alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Dispersion strengthening and fine grain strengthening can improve the corrosion resistance, radiation resistance, and high-temperature creep resistance of nuclear cladding materials. The formation and composition design parameters of typical oxides Y-Ti-O, Y-Al-O, and Y-Zr-O in oxide-dispersion-strengthened (ODS) FeCrAl alloys have a great influence on the properties of nuclear-industry-grade ODS FeCrAl alloys [ 9 ]. The perfluorosulfonic acid membrane composite of rare earth elements europium (III) and terbium (III) chlorides has a maximum dispersion and corresponding loss [ 10 ].…”
Section: Introductionmentioning
confidence: 99%